2009
DOI: 10.1021/jp900108a
|View full text |Cite
|
Sign up to set email alerts
|

On the Origin of the Decay of the Photocatalytic Activity of TiO2 Powders Ground at High Energy

Abstract: The influence of high-energy grinding on the photocatalytic activity of nanocrystalline titania (TiO2) powders was investigated. Either in gas or in liquid reactions, the photocatalytic activity is observed to decrease with milling time. The structural and surface characterizations showed that the catalytic decrease is not correlated to the milling induced transformation of anatase TiO2 into TiO2 rutile via the high-temperature and high-pressure phase TiO2-II but to the introduction of defects and to the amorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 84 publications
4
46
0
Order By: Relevance
“…1). The TiO 2 II phase was only identified in the P25 powder ground for 30 min as already reported and disappeared after heat treatment at 500°C [5]. The proportions of each phase and the mean grain sizes in the different samples have been calculated using the Rietveld method (Table 2) [31].…”
Section: Physico-chemical Properties Of the Tio 2 Materialsmentioning
confidence: 97%
See 1 more Smart Citation
“…1). The TiO 2 II phase was only identified in the P25 powder ground for 30 min as already reported and disappeared after heat treatment at 500°C [5]. The proportions of each phase and the mean grain sizes in the different samples have been calculated using the Rietveld method (Table 2) [31].…”
Section: Physico-chemical Properties Of the Tio 2 Materialsmentioning
confidence: 97%
“…In addition, an intermediate phase called TiO 2 II and isomorphous to α-PbO 2 was already encountered when anatase transforms into rutile under high energy ball milling [4,5]. Anatase is well-known to be more active in photocatalysis under UV light than the rutile allotropic form.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of milling on the phase transformation of titania with and without dopants has been widely investigated [141][142][143][144][145][146][147][148][149][150][151][152][153][154][155][156] because of the industrial interest in this material as a photocatalyst. It has been generally reported that the anatase -rutile transformation takes place through the intermediate formation of a non-equilibrium high-pressure phase.…”
Section: Oxidic Compoundsmentioning
confidence: 99%
“…Because of the difference in Fermi levels of anatase and rutile, the holes and electrons can be efficiently separated through charge carrier transfer. Hence, the mixed phase in TiO 2 may benefit the photocatalytic activity due to the reduced recombination between the excited electrons and holes, as found in the widely studied commercial Aeroxide P-25 TiO 2 [41].…”
Section: Xrd Patternsmentioning
confidence: 99%